Komunikasi Persuasif Iklan Layanan Masyarakat Kementrian Kesehatan Pada Media Youtube Tentang Edukasi Kangker Payudara - I Nyoman Miyarta Yasa; Ashar Banyu Lazuardi; Mohamad Yudisa Putrajip (Jurnal SASAK : Desain Visual dan Komunikasi, 2023)
In order to reduce breast cancer sufferers, the Indonesian Ministry of Health has made various efforts, one of which is creating Public Service Advertisements (PSAs) on YouTube social media. This research aims to find out what kind of PSAs support changes in people's behavior. This research uses a qualitative descriptive case study method. Data is analyzed using qualitative methods which are then presented and interpreted narratively or descriptively. The results of data analysis stated that the target community's behavior towards PSAs was quite positive. Most informants liked PSAs in the form of animations in the form of stories because they had a fear effect, thereby creating a desire to follow the invitation from the PSAs. Informants were of the opinion that the duration of the PSAs should not be too short so that it makes the PSAs less informative or should not be too long so that it makes the PSA boring. Informants stated that through PSAs, public or target audience awareness of breast cancer could be increased so that they were willing to follow the PSA's invitation.